2016
DOI: 10.1038/cddis.2016.257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of YM155 on survivin levels and viability in neuroblastoma cells with acquired drug resistance

Abstract: Resistance formation after initial therapy response (acquired resistance) is common in high-risk neuroblastoma patients. YM155 is a drug candidate that was introduced as a survivin suppressant. This mechanism was later challenged, and DNA damage induction and Mcl-1 depletion were suggested instead. Here we investigated the efficacy and mechanism of action of YM155 in neuroblastoma cells with acquired drug resistance. The efficacy of YM155 was determined in neuroblastoma cell lines and their sublines with acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 43 publications
8
57
2
Order By: Relevance
“…FOXL2 C134W induced targets are candidates for therapeutic intervention as they would be expected to show tumour specificity. SLC35F2, a putative direct target of FOXL2 C134W , encodes for a solute transporter previously shown to transport sepantronium bromide (YM155), a transcriptional suppressor of survivin expression having activity against a broad range of cancer types 47,48 (Fig. 5A).…”
Section: Foxl2 C134w Target Provides a Potential Therapeutic Vulnerabmentioning
confidence: 99%
“…FOXL2 C134W induced targets are candidates for therapeutic intervention as they would be expected to show tumour specificity. SLC35F2, a putative direct target of FOXL2 C134W , encodes for a solute transporter previously shown to transport sepantronium bromide (YM155), a transcriptional suppressor of survivin expression having activity against a broad range of cancer types 47,48 (Fig. 5A).…”
Section: Foxl2 C134w Target Provides a Potential Therapeutic Vulnerabmentioning
confidence: 99%
“…However, DNA damage induction and Mcl-1 depletion were later suggested as additional or alternative anti-cancer mechanisms of YM155 [5,[11][12][13][14][15]. We recently confirmed that YM155 exerts its anti-neuroblastoma effects predominantly through survivin suppression [7]. YM155-induced survivin suppression proceeded DNA damage formation.…”
Section: Introductionmentioning
confidence: 70%
“…YM155-induced survivin suppression proceeded DNA damage formation. Moreover, YM155 mimicked the effects of RNAi-mediated survivin depletion, whereas Mcl-1 depletion did not affect neuroblastoma cell viability [7]. Furthermore, YM155-adapted UKF-NB-3 neuroblastoma cells had developed resistance to RNAi-mediated survivin depletion [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations